Corporate Governance and Value Creation: Evidence from Private Equity - Acharya, Viral V.; Gottschalg, Oliver F.; Hahn, Moritz; Kehoe, Conor (Review of Financial Studies, 2013)
[Using deal-level data from transactions initiated by large private equity houses, we find that the abnormal performance of deals is positive on average, after controlling for leverage and sector returns. Higher abnormal performance is related to improvement in sales and operating margin during the private phase, relative to that for quoted peers. General partners who are ex-consultants or ex—industry managers are associated with outperforming deals focused on internal value-creation programs, and ex-bankers or ex-accountants with outperforming deals involving significant mergers and acquisitions. The findings suggest the presence, on average, of positive but heterogeneous skills at the deal-partner level in large private equity transactions.]